Answer:
Explanation:
Factorize the expression.
Sum = 7
Product = 12
Factors = 4 , 3
4 + 3= 7 & 4*3 = 12
x² + 7x + 12 = x² + 4x + 3x + 4*3
= x(x + 4) + 3(x + 4)
= (x + 4)(x + 3)
Sum = -1
Product = -12
Factors = (-4) , 3
(-4) + 3 = (-1) & (-4)*3 = -12
x² - x - 12 = x² - 4x + 3x - 4*3
= x(x - 4) +3(x - 4)
= (x -4)(x +3)
![\sf (x^(2)+7x+12)/(x^(2)-x-12)=((x+4)(x + 3))/((x -4 )(x + 3))\\\\\bf \text{(x +3) in the numerator and denominator will get cancelled}](https://img.qammunity.org/2023/formulas/mathematics/college/rld9nupwui2tp5pez1o09cnnwtxb4mase5.png)
![=(x+4)/(x-4)](https://img.qammunity.org/2023/formulas/mathematics/college/95g3imjt4z1q4u67jogt2kua2g7gzl1stc.png)